Study on salt deposition distribution and environmental effect of seawater cooling tower - Lujun Li; Qing Zhu; Xiaojun Song (Scientific Reports)
Abstract A three-dimensional numerical simulation model was developed to examine the dispersion and migration of droplets in large, naturally ventilated seawater cooling towers, as well as the pattern of salt deposition influenced by nearby buildings and crosswinds. Following a comprehensive hydrogeological survey at the site, we analyzed the effects of salt deposition on the salinity of surface water, paddy fields, and soil. Additionally, a seed planting trial was conducted to observe the growth of wheat in 11 different soil salinity conditions. The findings revealed that salt deposition did not alter the classifications of surface water quality, paddy water functionality, or soil salinization. However, soil salinity significantly affected the germination rate, bud length, bud fresh weight, and root-to-shoot ratio of the wheat variety Cangmai 6002. Assuming no erosion or dilution from rainfall, the soil salinity remained under 0.2% for 40 years, not impacting wheat yield.